ANALISIS EFEKTIVITAS PEMUNGUTAN PAJAK AIR TANAH SEBAGAI UPAYA MENINGKATKAN PENERIMAAN PAJAK DAERAH DI KOTA TERNATE - Taufik, Meisa Farina; Ilat, Ventje; Wangkar, Anneke (GOING CONCERN : JURNAL RISET AKUNTANSI, 2020)
The ground water tax is one of several local taxes levied in Ternate City which also plays a role in regional development. This study aims to determine the level of effectiveness of ground water tax collection in Ternate City and the amount of contributions made to the Ternate City regional tax and to determine the collection procedures imposed by the Ternate City Regional Tax and Retribution Management Agency as the authorized agency. This type of research uses qualitative methods with a descriptive approach. The results showed that ground water tax collection in Ternate was volatile. The effectiveness of the ground water tax for 2015-2016 gets very effective criteria the opposite is for 2017-2018, it gets ineffective criteria. This is because the target set in 2017-2018 rose to 100% and was not matched by the potential it had. The contribution of ground water tax in Ternate in 2015-2018 gets very less criteria, that is <2.5%. Groundwater tax collection procedure in Ternate City has been running well in accordance with applicable regulations. The stages of collection procedures are such as data collection and registration, determination, payment, supervision and reporting, billing.